2015
DOI: 10.2217/epi.15.32
|View full text |Cite
|
Sign up to set email alerts
|

The NSD Family of Protein Methyltransferases in Human Cancer

Abstract: The NSD family of protein lysine methyltransferases consists of NSD1, NSD2/WHSC1/MMSET and NSD3/WHSC1L1. NSD2 haploinsufficiency causes Wolf-Hirschhorn syndrome, while NSD1 mutations lead to the Sotos syndrome. Recently, a number of studies showed that the NSD methyltransferases were overexpressed, amplified or somatically mutated in multiple types of cancer, suggesting their critical role in cancer. These enzymes methylate specific lysine residues on histone tails and their dysfunction results in epigenomic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
126
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(129 citation statements)
references
References 64 publications
3
126
0
Order By: Relevance
“…Other reports have implied that NSD1 functions as a tumor suppressor gene, as we observed for ccRCC (20). Indeed, NSD1 silencing through CpG island-promoter hypermethylation has been frequently observed in neuroblastomas and gliomas and has predicted poor patient outcomes (11).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Other reports have implied that NSD1 functions as a tumor suppressor gene, as we observed for ccRCC (20). Indeed, NSD1 silencing through CpG island-promoter hypermethylation has been frequently observed in neuroblastomas and gliomas and has predicted poor patient outcomes (11).…”
Section: Discussionsupporting
confidence: 84%
“…Several studies have reported a possible oncogenic role for NSD1 in acute myeloid leukemia through the cryptic NLΓP98-NSD1 fusion t(5;ll)(q 35;p l5.5) (20). Other reports have implied that NSD1 functions as a tumor suppressor gene, as we observed for ccRCC (20).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the PRMT5 inhibitor identified in our laboratory has paved the way for future drug development to treat cancers and other disease with hyper PRMT5-driven NF-κB activity [22,39]. In addition to PRMT5, other histone methylases, such as NSD1, have been reported by us and others as a significant player in cancer development [20,[43][44][45]. Although researchers have been trying to develop a small NSD1 inhibitor for cancer treatment, no NSD1 specific inhibitor has yet been reported due to the large size of NSD1 enzyme and the lack of sufficiently sensitive assay development.…”
Section: Conclusion Perspective and Future Directionsmentioning
confidence: 92%
“…It is a member of the NSD protein histone lysine methyltransferase (HKMT) family, which also includes NSD1 (KMT3B) and NSD2 (WHSC1/MMSET). 11 The NSD HKMT family proteins are responsible for methylation of lysine 36 on histone H3 (H3K36me2) and works as an important epigenetic factor with implicated roles in breast and lung cancer. 12,13 NSD3, located on chromosome 8p12, was first discovered to be amplified in breast cancer, suggesting its potential oncogenic ability.…”
mentioning
confidence: 99%
“…The short isoform (NSD3S) is produced by alternative splicing and only has one PWWP domain, and lacks six chromatin reader domains and the SET domain with the catalytic activity. 11 The whistle isoform shares the C-terminal region with the NSD3L, containing the SET domain. 15,16 Although NSD3S does not have the methylation catalytic activity, it is required for the acute myeloid leukemia maintenance through bridging BRD4 to CHD8, working as an oncoprotein, 17 suggesting its crucial role in leukemia.…”
mentioning
confidence: 99%